Comparative examination of a mineral fertiliser and a bacterial fertilizer on humic sandy soil - Tállai, Magdolna (Acta Agraria Debreceniensis, 2010)
In our pot experiment, the impact of a bacterial fertilizer, Bactofil® A10 and a mineral fertilizer Ca(NO3)2 applied in different rates was studied on some soil chemical and microbiological characteristics of a humic sandy soil (Pallag). Perennial rye-grass (Lolium perenne L.) was used as a test-plant. Samples were collected four and eight weeks after sowing in each year. The experiment was set up in 2007-2009 in the greenhouse ofthe UD CASE Department of Agrochemistry and Soil Science. The available (AL-extractable) nutrient contents of soil, among the microbial parameters the total number of bacteria, the number of microscopic fungi, cellulose-decomposing and nitrifying bacteria, the sacharase and urease enzyme activity, as well as the soil respiration rate were measured.Statistical analyses were made by means of the measurements deviation, LSD values at the P=0.05 level and correlation coefficients were calculated. Results of our experiment were summarised as follows:− The readily available nutrient content of humic sandy soil increased as affected by the treatments, in case of the available (AL-extractable) phosphorus and potassium content the higher value was measured in high-dosage artificial fertilizer treatment.− The treatments had also positive effect on several soil microbial parameters studied. The higher-dosage mineral fertilizer treatments had a beneficial effect on the total number of bacteria, cellulose-decomposing and nitrifying bacteria. No significant differences were obtained between the effect of treatment in case of the total-number of bacteria, the number of microscopic fungi and nitrifying bacteria.− On the sacharase enzyme activity the artificial fertiliser treatments proved to be unambiguously stimulating, the urease activity significantly increased on the effect of the lower-dosage Ca(NO3)2 artificial fertilizer treatment. − The soil respiration increased in all treatments in related to the amounts applied, significantly increased in the highest rate of Ca(NO3)2 fertilizer addition. − Some medium and tight positive correlations were observed between the soil chemical and microbiological parameters studied in case of both nutrient sources. Summarizing our results, it was established that the organic and all the mineral fertilizer treatments had beneficial effects on the major soil characteristics from the aspect of nutrient supply. In majority of the examined soil parameters (AL-extractable phosphorus- and potassium, total number of bacteria, number of cellulose-decomposing and nitrifying bacteria, activity of sacharase enzyme) the high rate of Ca(NO3)2 mineral fertilizer treatment proved to be more stimulating, but at the same time the high rate bacterium fertilizer resulted in significant increases inthe nitrate-N content, the AL-potassium content of soil, the total number of bacteria, the number of cellulose-decomposing and nitrifying bacteria and the urease enyme activity. Our examinations showed that the mineral fertilizer treatments proved to be more stimulating on most of the soil parameters studied but according to our results, it was established that Bactofil is efficiently applicable in the maintenance of soil fertility and the combined application ofmineral fertilizer and bacterium fertilizer may be a favourable opportunity – also in aspect of the environmental protection – in maintaining soil fertility.